To donate or not to donate: meanings of family refusal to the refusal to donate organs and tissues - Fontenele, Rafael Mondego; Costa, Nivilly Reis; Moraes, Luiza Maria de Nóvoa; Silveira, Walkíria Jéssica Araújo; Almeida, Hariane Freitas Rocha (Revista de Enfermagem da UFPI, 2023)
Objective: To understand the meanings attributed by family members about the refusal to donate organs and tissues. Methods: A descriptive and exploratory study with a qualitative approach. A semi-structured questionnaire was used for data collection and thematic content analysis was employed for the treatment of the data obtained. The sample comprised by 10 participants was defined by means of the theoretical saturation criterion. Results: There was a tendency for family members to consent to the donation when well-oriented about brain death and the humanistic purpose of the donor, but the main obstacles to refuse donation are as follows: lack of knowledge about organ donation, fear of body mutilation for not knowing how the procedure for removing organs and tissues is performed, bureaucracy with the delay in releasing the body for burial and disagreement between family members. Conclusion: The meanings of family refusal permeate fear, a feeling of emptiness and lack of information about the processes involved in organ and tissue donation, as well as cultural and religious aspects, although despair, pain and lack of empathy of the health teams can also corroborate refusal.